Knowledge and Critical Pedagogy : An Introduction - Kincheloe, Joe L (Springer, 2008)
This book takes scholars through a critical review of the issues facing researchers and educators in the last years of the first decade of the twenty-first century. Refusing to assume the reader?s familiarity with such issues but concurrently rebuffing the tendency to dumb down such complex issues, the book serves as an excellent introduction to one of the most important and complicated issues of our time. An introduction takes scholars through a critical review of the issues facing researchers and educators in the last years of the first decade of the twenty-first century.